Credit nation : property laws and legal institutions in early America - Priest, Claire (Princeton economic history of the Western world., 2021)
How American colonists laid the foundations of American capitalism with an economy built on credit. Even before the United States became a country, laws prioritizing access to credit set colonial America apart from the rest of the world. Credit Nation examines how the drive to expand credit shaped property laws and legal institutions in the colonial and founding eras of the republic.